2016
DOI: 10.1177/1708538116644871
|View full text |Cite
|
Sign up to set email alerts
|

The use of intrarenal Doppler ultrasonography as predictor for positive outcome after renal artery revascularization

Abstract: Whether patients with renal artery stenosis should undergo therapeutic revascularization is controversial. In this retrospective study, we evaluated prognostic intrarenal Doppler ultrasound parameters that might have a predictive value for a beneficial response after renal revascularization. From January 2003 until December 2012, all renovascular interventions for renal artery stenosis were analyzed. The resistive index and the maximal systolic acceleration were determined by Doppler ultrasonography prior to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…Previous research 13,[15][16][17][18] and our study both show that ACC max is a feasible noninvasive technique for assessing the severity of PAD and renal artery stenosis. In contrast, other duplex parameters are limited to identify the severity of a PAD (particularly at multilevel stenoses).…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…Previous research 13,[15][16][17][18] and our study both show that ACC max is a feasible noninvasive technique for assessing the severity of PAD and renal artery stenosis. In contrast, other duplex parameters are limited to identify the severity of a PAD (particularly at multilevel stenoses).…”
Section: Discussionsupporting
confidence: 68%
“…To circumvent this bias, maximal systolic acceleration (ACC max ) was introduced. Importantly, ACC max has been shown to have diagnostic value in renal artery stenosis, [15][16][17][18] and van Tongeren et al 13 and Buschmann et al 14 showed that ACC max is an accurate noninvasive tool for diagnosing PAD, also in diabetic patients who often have a higher degree of medial calcific sclerosis. In addition, determining the severity of PAD in patients with CLI can be challenging as a result of the presence of noncompressible arteries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bardelli et al 18 described the novel ACCmax in 2006 for detection of renal artery stenosis. Subsequently several clinical studies were published about the ACCmax in renal artery stenosis 17,19,20 and peripheral artery diseases of the lower extremity 15,16 , however without investigating the interobserver agreement clinically. A previous in vitro study 14 revealed a good interobserver agreement for ACCmax (intraclass correlation coefficient of 0.99) and a good correlation between ACCmax and intra-arterial pressure gradient (R 2 0.937) was found.…”
Section: Discussionmentioning
confidence: 99%
“…8,[10][11][12][13] A relatively new velocimetric doppler-derived parameter, maximal systolic acceleration (ACCmax), has been evaluated in atherosclerotic diseases. [14][15][16][17][18][19][20] Recently we established in an in vitro study that a decreased ACCmax correlated very well with an increasing severity of stenosis, and a good correlation was found between the ACCmax and the intra-arterial pressure gradient (coefficient of determination (R 2 ) of 0.937). 14 A high ACCmax value endorses that there is no hemodynamic inflow problem and excludes the presence of peripheral artery disease.…”
Section: Introductionmentioning
confidence: 99%